Molecular profiling of pancreatic neuroendocrine tumors (pNETS) and the clinical potential. (4th May 2018) - Camilli, Massimiliano; Papadimitriou, Konstantinos; Nogueira, Amanda; Incorvaia, Lorena; Galvano, Antonio; D'Antonio, Federica; Ferri, Jose; Santini, Daniele; Silvestris, Nicola; Russo, Antonio; Peeters, Marc; Rolfo, Christian
ABSTRACT: Introduction : Pancreatic neuroendocrine tumors (pNETs) represent a small part of pancreatic neoplasms, and the knowledge about their indolent clinical course remains a subject of investigation. They occur sporadically or as part of familial cancer syndromes and are classified by WHO in 3 categories. There is ongoing research to understand their molecular profiling and leading mutations. Areas covered : The aim of this review is to clarify the overall aspects of tumorigenesis, to expose the latest developments in understanding the course of the disease and the possible therapeutic implications of these. The review also discusses functional and non-functional pNETs and associated inherited syndromes as well as pNET molecular profiling and its possible guidance in the use of targeted therapy. Expert commentary : In the next decade, a more extensive application of new technologies will help improve quality of life and survival, individualizing treatment protocols and identifying which therapeutic strategy is more suitable for each kind of NET.